One-dimensional hydrodynamic simulations of low convergence ratio direct-drive inertial confinement fusion implosions. (7th December 2020) - Paddock, R. W.; Martin, H.; Ruskov, R. T.; Scott, R. H. H.; Garbett, W.; Haines, B. M.; Zylstra, A. B.; Aboushelbaya, R.; Mayr, M. W.; Spiers, B. T.; Wang, R. H. W.; Norreys, P. A.
Abstract : Indirect drive inertial confinement fusion experiments with convergence ratios below 17 have been previously shown to be less susceptible to Rayleigh–Taylor hydrodynamic instabilities, making this regime highly interesting for fusion science. Additional limitations imposed on the implosion velocity, in-flight aspect ratio and applied laser power aim to further reduce instability growth, resulting in a new regime where performance can be well represented by one-dimensional (1D) hydrodynamic simulations. A simulation campaign was performed using the 1D radiation-hydrodynamics code HYADES to investigate the performance that could be achieved using direct-drive implosions of liquid layer capsules, over a range of relevant energies. Results include potential gains of 0.19 on LMJ-scale systems and 0.75 on NIF-scale systems, and a reactor-level gain of 54 for an 8.5 MJ implosion. While the use of 1D simulations limits the accuracy of these results, they indicate a sufficiently high level of performance to warrant further investigations and verification of this new low-instability regime. This potentially suggests an attractive new approach to fusion energy. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.